Tanreqing Inhibits LPS-Induced Acute Lung Injury In Vivo and In Vitro Through Downregulating STING Signaling Pathway - He, Yu-Qiong; Zhou, Can-Can; Deng, Jiu-Ling; Wang, Liang; Chen, Wan-Sheng (Frontiers in Pharmacology, 2021)
Acute lung injury (ALI) is a common life-threatening lung disease, which is mostly associated with severe inflammatory responses and oxidative stress. Tanreqing injection (TRQ), a Chinese patent medicine, is clinically used for respiratory-related diseases. However, the effects and action mechanism of TRQ on ALI are still unclear. Recently, STING as a cytoplasmic DNA sensor has been found to be related to the progress of ALI. Here, we showed that TRQ significantly inhibited LPS-induced lung histological change, lung edema, and inflammatory cell infiltration. Moreover, TRQ markedly reduced inflammatory mediators release (TNF-α, IL-6, IL-1β, and IFN-β). Furthermore, TRQ also alleviated oxidative stress, manifested by increased SOD and GSH activities and decreased 4-HNE, MDA, LDH, and ROS activities. In addition, we further found that TRQ significantly prevented cGAS, STING, P-TBK, P-P65, P-IRF3, and P-IκBα expression in ALI mice. And we also confirmed that TRQ could inhibit mtDNA release and suppress signaling pathway mediated by STING in vitro. Importantly, the addition of STING agonist DMXAA dramatically abolished the protective effects of TRQ. Taken together, this study indicated that TRQ alleviated LPS-induced ALI and inhibited inflammatory responses and oxidative stress through STING signaling pathway.